Pastoralist Mobility along the Sudanese Ethiopian Borderland: Towards Cooperative Land Management - Hussein M. Sulieman; Adam Babekir; Abdel Ghaffar M. Ahmed (Nomadic Peoples, 2024)
This study followed an interdisciplinary mixed approach that consisted of social research methods and geospatial technology to investigate the livestock mobility of four pastoralist groups from Sudan and two Ethiopian pastoralist groups who fled to Sudan due to the conflict in the Tigray region. The study area is a shared borderland located between the two countries and is part of Gadarif State in Sudan and the Tigray and Amhara regions in Ethiopia. The findings of the study showed that there are diverse types of pastoral mobility in the borderland, ranging from short and circular movement to wide and directional type of mobility in response to seasonal variations, the spread of mechanised farming and the eruption of insecurity events. Despite facing numerous challenges including the governments’ restrictions on cross-border movement and the prevalence of looting and rustling, trans-boundary mobility is practised by most pastoralist groups in the borderland. Pastoralist leaders are playing an important role in facilitating cross-border mobility. The recent conflict in the Tigray region forced many Ethiopian pastoralists to flee to Sudan with their animals, and they have had to cope with this situation by reducing the number of head they own and limiting their mobility to a more confined area. Despite competing claims by both governments, there is a pressing need for a cooperative land management policy applying soft border arrangements that incorporate customary land use rights for pastoralists from both sides, instead of the hardline border policies currently in place.